#TITLE_ALTERNATIVE# - AKHSANUR ROFI (NIM 13003099), M.
Membrane Crystallizer (MCr) is an emerging novel technique in separation process. A conventional pressure-based membran system used in sea water desalination such as reverse osmosis or traditional distillation system such as multi-effect distillation and multi-stage flash produce efluent of waste brine solution that could harm the environment. The pollutant of which could be treated efficiently and economically by integrating crystallizer with downstream process of membran distillation (MD). MCr membrane material act as contactor which allow vapour molecule and reject the nonvolatile solute in the solution. This phenomenon is applied in producing salt crystals and pure water simultaneously on the sea water treatment. The drawback of the process is formation of the crystals on the membrane pore which could decreasing flux due to fouling, wetting, and doule polarization mechanism. Salt concentration control has become a major point in the development of membrane crystallizer. This research's focus is to observe the efect of salt concentration to the vacuum reverse osmosis (VRO) performance and also study the efect of temperature to the vacuum membrane distillation (VMD) performance. The modules that are used is porous hydrophobic membrane and dense hydrophilic membrane. This research shows that in the flow speed of 9 L/h and temperature between 30-50 degrees C, VMD's permeate flux is below the theoritical value but still having almost 100% rejection. The observation in VRO performance shows that VRO has potential to become a support membrane for membrane distillation due to it's stability in high concentration of feed.